Converting an intensity-based sensor to a ratiometric sensor: luminescence colour switching of an Ir/Eu dyad upon binding of a V-series chemical warfare agent simulant. Issue 41 (10th October 2016) - Metherell, Alexander J.; Curty, Christophe; Zaugg, Andreas; Saad, Suad T.; Dennison, Genevieve H.; Ward, Michael D.
Abstract : A dual-luminescent Ir(iii )–Eu(iii ) sensor is reported which changes luminescence colour from red to blue in the presence of a chemical warfare agent simulant. Abstract : Interaction of the V-series chemical warfare agent simulant 'VO ' with Eu(iii ) results in selective quenching of the red Eu-based emission component from a dual-luminescent (blue/red) Ir(iii )/Eu(iii ) dyad, resulting in a colour change in the luminescence from red to blue in the presence of the simulant.